Cats [compact disc] : complete original Broadway cast recording. - Eliot, T. S. (Thomas Stearns), 1888-1965 (Decca U.S., 2005)
This is the show that launched the blockbuster musical movement and played 18 years on Broadway. The unsurpassed original Broadway cast recording features the sensational Betty Buckley and her unforgettable rendition of the hit Memory.